Functional Non‐Volatile Memory Devices: From Fundamentals to Photo‐Tunable Properties (Phys. Status Solidi RRL 5/2019). Issue 5 (10th May 2019) - Wang, Zhanpeng; Zhang, Shi‐Rui; Zhou, Li; Mao, Jing‐Yu; Han, Su‐Ting; Ren, Yi; Yang, Jia‐Qin; Wang, Yan; Zhai, Yongbiao; Zhou, Ye
Abstract : In article number1800644, Su‐Ting Han, Ye Zhou and coworkers present a critical review on the recent developments of functional memories. First, three‐terminal field effect transistor memory is introduced, while metal oxides, organic semiconductors and 2D materials are mainly discussed for the construction of the semiconductor channel. The resistive random access memory (ReRAM) is then presented. Resistive switching phenomena exist in various kinds of materials such as oxides, polymers and 2D materials. The researches on these materials and their applications on ReRAM are reviewed systematically. In the final part, novel photo‐tunable memory is introduced. Based on the basic structure of these memory devices, photo‐tunable materials can be further used to bring in light modulation.